Conversion of Kappaphycus alvarezii macroalgae biomass enriched with fulvic acid into a foliar biostimulant for plant (Oryza sativa L.) growth and stress protection - Tadeu Augusto van Tol de Castro; Danielle França de Oliveira Torchia; Ayhessa Cristina Santos de Lima; Samuel de Abreu Lopes; Raphaella Esterque Cantarino; Natália Fernandes Rodrigues; Erinaldo Gomes Pereira; Vinicius Olivieri Rodrigues Gomes; Leandro Azevedo Santos; Ana Lúcia do Amaral Vendramini; Andrés Calderín García (Chemical and Biological Technologies in Agriculture)
Abstract Background The incorporation of circular economy into agricultural processes is necessary to improve the efficiency of agronomic practices in the future. The biomass of macroalgae as well as humic substances is sustainable options for stimulating the efficient use of nutrients in plants. This study aimed to evaluate the modes of action of a potential plant biostimulant composed of an aqueous extract of Kappaphycus alvarezii seaweed plus fulvic acid (KAF) applied to rice (Oryza sativa L.) leaves. The aqueous extract was obtained from the fresh biomass of the macroalga Kappaphycus alvarezii and the fulvic acid was extracted from a cattle manure vermicompost (FAVC). Both fractions (KAlv-sap and FAVC) were characterized using 1H NMR. The bioactivity of KAF was evaluated in experiments with four treatments: control (foliar application of water), FAVC (foliar application of FAVC), KAlv-sap (foliar application of seaweed extract), and KAF (foliar application of FA + KAlv-sap). In rice, the expression of genes related to K+ and N transport, plasma membrane H+-ATPases, and oxidative stress defense enzymes were evaluated. Metabolites and N, K, and P contents, as well as photosynthetic efficiency and root morphology, were quantified. Results The 1H-NMR spectra showed that KAF is rich in organic fragments such as sugars, nitrogenous, aromatic, and aliphatic compounds in general. Foliar application of KAF resulted in a 7.1% and 19.04% increase in the dry mass of roots and leaves, respectively. These plants had 19% more roots and 11% more total root length. The application of KAF increased in the plant sheaths the N and K contents by up to 50% and 14%, respectively. Conclusions The mechanism of action by which KAF triggered these changes seemed to start with an improvement in the photosynthetic efficiency of plants and regulation through increased expression and suppression of genes related to K+, N, H+-ATPase transporters, and oxidative metabolism. KAF might become a sustainable plant biostimulant that promotes plant growth, development, and defense against abiotic stresses. Graphical Abstract